The development of ArtHis interactive module in teaching and learning art history / Aliza Mohd Salleh - Mohd Salleh, Aliza (2017)
The publishing material of Art History pedagogy is known to have too many facts and students need to digest lots of information. The alternative methods of teaching and learning have become more reliable when technology-based methods have been found to be an effective pedagogical material. This study aims to design and develop an ArtHis Interactive Module for teaching and learning Art History in Visual Art Education. For this reason, this study also investigates the impact of its usability in classroom and assesses the learning motivation of Visual Art students‟ simultaneously. In this study, the Design and Developmental Research (DDR) method was used. For the most part, the ArtHis Interactive Module is developed by using ADDIE Model by considering the elements of design, technical, pedagogical, and the content which is appropriate to achieve the objectives stated in Visual Art Education syllabus. Specifically, the development process was guided and supported by Dual Coding Theory and Flow Theory for information processing. For this purpose, the research focused on Form Five Visual Art students. Microsoft PowerPoint was used to produce the interactive module with the aim of enhancing the students‟ motivation in learning Art History. The finding shows that the impact of learning Art History using ArtHis Interactive Module has improved students‟ conceptual understanding. The findings from the pre-test mean = (1.258) was compared in post-test mean (2.897) which showed students‟ motivation in learning Art History has improved after using the interactive module. The findings (p-value= 0.706) stated that there is no significant difference which proves each male and female is ready to receive instruction through the implementation of ArtHis Interactive Module elements. It is also determined that 93.9% students agree that the exercises in the Arthis Interactive Module help them to gauge their level of understanding and knowledge on the topics in Art History. In conclusion, ArtHis Interactive Module is used for the purpose of improving teaching methods and increasing the motivation of students in Visual Art Education especially Art History topics.